Technological Pedagogical and Content Knowledge (TPACK) on Mathematics Learning: A Systematic Review - Etika Khaerunnisa; Asep Muhyidin; Sjaifuddin Sjaifuddin; Yuyu Yuhana (Gemilang Maju Publikasi Ilmiah (GMPI), 2025)
This study aimed to determine the extent of research using TPACK on Mathematics Learning. This Systematic Review used the PRISMA method and, with the help of the Publish or Perish and VOS Viewer software applications, obtained 142 articles from journals sourced from Scopus. The article journal is related to using the TPACK method in mathematics learning. It was found from the results of the literature review that the study of TPACK keywords could be categorized into (1) TPACK on the use of teaching/learning devices/tools and the development of learning innovations; (2) TPACK in learning planning; and (3) TPACK in evaluating teacher competency. The author believes that applying TPACK in mathematics learning requires careful planning and clear output/outcomes, so using tools can also provide optimal benefits. However, it must still be coupled with qualified teaching teachers' competence.